Cold stress induces colitis-like phenotypes in mice by altering gut microbiota and metabolites - Sun, Lijuan; Wang, Xueying; Zou, Yuankang; He, Yixuan; Liang, Changting; Li, Juan; Li, Pu; Zhang, Jianbin (Frontiers in Microbiology, 2023)
The modernized lifestyle has been paralleled by an epidemic of inflammatory bowel disease (IBD). Excessive consumption of cold beverages is especially common among the modern humans. However, whether cold stress contributes directly to the gut barrier and gut-brain axis is not clear. We conducted a cold stress model induced by cold water. The mice were treated with 14 consecutive days of intragastric cold or common water administration. We observed changes in gut transit and gut barrier in the colon. We also employed RNA sequencing-based transcriptomic analysis to identify the genes potentially driving gut injury, and simultaneously examined the gut microbiota and metabolites in the feces. We found that cold stress disturbed the intestinal function and increased gut permeability. A set of core genes related to immune responses were consistently overexpressed in the cold stress group. Additionally, cold stress induced decreased bacterial diversity, ecological network and increased pathogens mainly belonging to Proteobacteria. The dopamine signaling pathway-related metabolites were largely reduced in the cold stress group. This study revealed that cold stress could trigger an IBD-like phenotype in mice, implying that cold stress is a possible risk factor for IBD development.